Bean mutant induced by ionizing radiation. III. Wrinkled Leaf - Moh, C.C. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A bean mutant called Corrugated Leaf was isolated from the progeny of the third generation (R3) whose parents were exposed to a chronic dose of gamma radiation of 75 r per day for 30 days. The mutant has dark green, corrugated leaves that are thicker than normal. Genetic studies revealed that the corrugated leaf trait is recessive and due to a single gene.